RUDOLPH OTTO'S IDEA OF THE HOLY: A REAPPRAISAL - Ware, Owen (Heythrop journal, 2007)
This paper explores the ambiguity in Rudolph Otto's discussion of the mysterium tremendum in order to address a broader set of difficulties in The Idea of the Holy (1917). In doing so, I outline two common criticisms of Otto's position. The first attacks Otto for not providing a secure transition from the numinous experience of terror to the holy experience of faith. The second attacks Otto for upholding a kind of theistic dualism, which seemingly puts his thought at odds with mysticism. Rather than reconstruct Otto's argument in favour of theism, I maintain that numinous experience, while still a form of otherness or alterity, is best characterized as the breakdown of subject-object dualism. I further suggest that this breakdown is best understood in non-theistic terms. For examples of the latter, I briefly turn to Jean-Luc Marion's notion of saturated phenomena.